Arsitektur Perilaku dan Adaptasi Fungsi Spasial Jalur Pedestrian Menjadi Sentra Kuliner Jalan Panjaitan Kota Gorontalo - Fitra B Antula; Heryati; Rifana Ramli; Asniyati Yasin; Moh. Mq Abdullah; Ririn Syafriyani (Politeknik Kebangsaan, 2026)
The functional shift of pedestrian pathways into informal commercial hubs frequently triggers spatial challenges, creating a discrepancy between formal infrastructure design and actual community behaviors. This study aims to analyze the reciprocal relationship between the physical setting of post-revitalization sidewalks and user behavior patterns, evaluate public perception, and formulate sustainable spatial design recommendations along the Jalan Panjaitan (Jalan Nani Wartabone) corridor in Gorontalo City. Guided by behavioral architecture approaches based on Amos Rapoport's and Jan Gehl's theories, this research employs a descriptive-analytical sequential mixed-methods approach. Qualitative data were gathered through direct observation, visual documentation, and behavioral mapping (place-centered mapping, person-centered mapping, and physical trace) across four daily temporal segments (morning, afternoon, evening, and night). Meanwhile, quantitative data were derived from structured questionnaires distributed to 52 respondents selected via accidental sampling. The spatial-behavioral analysis reveals an elastic functional transformation of the pedestrian pathway; it effectively functions as a space of movement for active mobility and sports during the morning and afternoon, yet shifts significantly into a space of staying for social interaction and informal culinary activities during the evening and night. Public perception evaluation indicates a remarkably high social acceptance rate of 84.62%, as the culinary zone is perceived to enhance urban vibrancy and stimulate the microeconomy, despite introducing urban challenges such as reduced pedestrian clear paths and traffic congestion due to on-street parking overflows. Consequently, this study recommends the implementation of behavioral engineering through temporal zoning regulations for operational time sharing, the provision of centralized off-street parking facilities, and the integration of portable sanitation systems.